Systematic Literature Review on the Integration of Total Quality Management and Green Manufacturing in Enhancing Sustainable Manufacturing Competitiveness - Nova Wisnianingsih; Nilda Tri Putri; Alizar Hasan; Franka Hendra (JTI: Jurnal Teknik Industri, 2026)
Global pressures on the manufacturing industry to enhance competitiveness while simultaneously meeting sustainability demands have intensified the need for integrated managerial approaches. Total Quality Management (TQM) has long been recognized as a fundamental driver of organizational performance through continuous improvement and customer orientation, while green manufacturing has emerged as a key strategy for reducing the environmental impacts of production processes. However, existing literature indicates that these two approaches are often implemented in isolation, limiting their potential synergy in building sustainable manufacturing competitiveness. This article aims to conduct a Systematic Literature Review (SLR) to comprehensively examine the integration of TQM and green manufacturing and its contribution to enhancing manufacturing competitiveness. The SLR method was applied by reviewing peer-reviewed and reputable scientific publications from the past five years, including empirical studies, conceptual frameworks, and prior systematic reviews. The findings reveal that TQM functions as an organizational capability that facilitates the adoption of green manufacturing practices through the strengthening of quality culture, leadership commitment, and employee involvement. The integration of TQM and green manufacturing is shown to have a positive impact on sustainability performance, environmental performance, green innovation, and competitive advantage in manufacturing firms. This study contributes by developing an integrative conceptual framework that positions TQM as a strategic enabler of green manufacturing within the context of sustainable manufacturing competitiveness, while also identifying research gaps and future research agendas, particularly in developing countries.